Generalizing Monotonicity Inferences to Opposition Inferences - Chow, Ka-fat (Proceedings of the Amsterdam Colloquium, 2011)
This paper generalizes the notion of monotonicities to op position properties (OPs). Some propositions regarding the OPs of de terminers will be proposed and proved. We will also define the notion of OP-chain and deduce a condition that enables us to determine the OPs of an iterated quantifier in its predicates based on the OPs of its constituent determiners.